Multiple allergies to metal alloys - Mei-Eng Tu; Yu-Hung Wu (Wolters Kluwer Medknow Publications, 2011)
Background: Metals are well-known allergens that are most commonly encountered as alloys rather than as the pure substance. However, induction of multiple metal allergies by alloys has not been widely reported. Objective: The aim of this study was to evaluate the prevalence of multiple metal allergies in metal-allergic patients. Methods: From August 1996 to September 2008, 97 patients (53 females and 44 males) in whom metal dermatitis was suspected were patch tested with the European standard series and a metal series. Age, sex, location of skin rash, occupation, specific metal allergies, and possible sources of sensitization were analyzed. Results: Positive patch test reactions were seen in 55% (53 of 97) of patients, of whom 21 (40%) were allergic to more than one metal. Nearly three-quarters were sensitized to nickel and to at least one other metal, most commonly palladium, cobalt, or gold. Jewelry, eyeglass frames, watch straps, and buttons were common sources of allergies to multiple metals. Conclusions: Metal alloys may induce multiple metal allergies. Patients suspected of having a metal allergy should be patch tested with an extended series of metals. We recommend adding palladium and gold, at least, to the standard series.